PENERAPAN PUBLIC PRIVATE PARTNERSHIP DALAM E-GOVERNMENT (STUDI KASUS: DINAS KEBUDAYAAN, KEPEMUDAAN, DAN OLAHRAGA SERTA PARIWISATA KOTA SURABAYA) DENGAN E-TICKET WISATA - Putri, Allicia Syafira; Fatria, Deni Yuda; Anjarwati, Christia; Yulika, Ikhlima Rahma; Anggraini, Puspita; Darna, Krisna Dwi; Eprilianto, Deby Febriyan (Publika, 2025)
E-Government is a popular term in recent years. E-Government as a form to improve the government system which aims to increase the productivity and quality of public services that are more effective, efficient and transparent. However, the implementation of E-government has in fact not run smoothly. This is due to certain obstacles such as lack of finance, lack of IT operational capabilities, etc. The concept of public private partnership (PPP) emerged as a solution to obstacles that arise in the implementation of e-Government. Several government agencies have successfully implemented e-Government and have good quality public services. One of them is the Surabaya City Culture, Youth, and Sports and Tourism Office which provides innovative online-based public services such as e-Tickets for Surabaya tours, e-Catalog Museums, BeSmart, and so on. The focus of this research is the innovation of the Surabaya tourism e-ticket service. This is intended to highlight how the Department of Culture, Youth, Sports and Tourism of the City of Surabaya can run the e-government and private parties who are cooperating as an effort to optimize and introduce tourist areas in the City of Surabaya.